New methods of treatment for severe and moderate postoperative pain syndrome in patients with cancer - D.V. Dmytriiev; M.M. Barsa (Медицина неотложных состояний)
Background. Anesthesia management in oncology surgeries poses significant challenges for anesthesiologists due to the extent of surgical trauma and the presence of pre-existing conditions such as chronic pain and prolonged use of narcotic analgesics. This necessitates the development of novel strategies to optimize postoperative pain management, particularly in this cohort. Objective: to evaluate the clinical efficacy and safety of a medicinal product with active ingredient dinalbuphine sebacate (150 mg/2 ml) in patients with moderate to severe pain syndrome following reconstructive mammoplasty due to breast cancer surgery. Materials and methods. This was a multicenter, randomized, prospective, open-label study involving 60 inpatients who underwent mammoplasty as a result of breast cancer surgery. Both groups received medications in accordance with multimodal analgesia protocols (paracetamol 1 g four times daily, dexketoprofen 50 mg three times daily, additional doses of non-steroidal anti-inflammatory drugs (NSAIDs) as needed) and morphine as needed at a maximum dose of 40 mg/day. Patients in the experimental group (30 participants) received 150 mg of dinalbuphine sebacate intramuscularly 12–24 hours before surgery. The primary endpoints included pain intensity measured on a numerical rating scale at 6, 24, 48, 96, and 120 hours postoperatively, the number of doses of NSAIDs and morphine as needed, and the incidence and nature of complications associated with drug administration. Results. A statistically significant difference in pain levels on the numerical rating scale was observed at 6 and 24 hours (p < 0.05). After 48, 96, and 120 hours, pain levels did not differ between the groups. Morphine consumption differed significantly between the experimental and control groups on the first postoperative day (0 [0; 10] mg vs. 10.0 [0; 10] mg, respectively, p < 0.05). On the second day, the values were 0 [0; 10] mg vs. 0 [0; 10] mg, respectively, p = 0.232. Additional NSAIDs administration was required by 83.3 % of patients in the experimental group and 93.4 % of controls. Conclusions. The study demonstrated that dinalbuphine sebacate is an effective and safe component of multimodal analgesia. In the experimental group, target levels of postoperative pain control were achieved during the first 24 hours following surgery, unlike the control group.